2018
DOI: 10.1002/tafs.10078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Trade‐Offs between Invasion and Isolation for Native Brook Trout and Nonnative Brown Trout in Pennsylvania Streams

Abstract: A popular conservation strategy for native trout species in western North America is to prevent invasions by nonnative trout by installing barriers that isolate native trout populations into headwater streams. In eastern North America, native Brook Trout Salvelinus fontinalis are frequently replaced in coolwater habitats by nonnative Brown Trout Salmo trutta and relegated to small headwater streams. In this study, we compared the effects of isolation and invasion by nonnative Brown Trout on the distribution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 51 publications
(201 reference statements)
1
23
0
Order By: Relevance
“…The results of our study are in congruence with the other documented observations of the impacts of the invasive trout on the distribution of the native species across the globe (Larson and Moore, 1985;Fausch 2008;Hoxmeier and Dieterman, 2013). Owing to its aggressive territoriality, the Brown Trout has been found to exclude the native fishes, distinctively relegating them to the headwater or the smaller order tributaries (Fausch and White, 1986;Kirk et al, 2018). Owing to higher numbers of the Brown Trout adults in the downstream segments, the Snow Trout seemingly maintains higher numbers in the upstream segments.…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study are in congruence with the other documented observations of the impacts of the invasive trout on the distribution of the native species across the globe (Larson and Moore, 1985;Fausch 2008;Hoxmeier and Dieterman, 2013). Owing to its aggressive territoriality, the Brown Trout has been found to exclude the native fishes, distinctively relegating them to the headwater or the smaller order tributaries (Fausch and White, 1986;Kirk et al, 2018). Owing to higher numbers of the Brown Trout adults in the downstream segments, the Snow Trout seemingly maintains higher numbers in the upstream segments.…”
Section: Discussionsupporting
confidence: 90%
“…Instead, one of our plausible models indicated that Brown Trout CPUE was positively related with Brook Trout occupancy, potentially because Brown Trout use similar thermal and physical habitats as Brook Trout for feeding and reproduction (i.e., pools and coarse substrates; Fausch and White 1981; Witzel and MacCrimmon 1983) and Brown Trout have likely colonized—either through past stockings or immigration—the last remaining stream segments where Brook Trout persist. Despite finding no evidence for adverse interactions between species in this study, proactive conservation actions, such as the isolation of Brook Trout populations above barriers or the removal of Brown Trout from sympatric sites, have resulted in improved survival, abundance, and size structure of Brook Trout (Hoxmeier and Dieterman 2016; Kirk et al 2018; Miller et al 2019) and may be pertinent options for states attempting to manage fisheries for both species.…”
Section: Discussionmentioning
confidence: 74%
“…With surmounting evidences of native ecosystem collapses resulting from its invasions in most mountain systems (Boddy, 2018;Fausch & White, 1981;Kirk et al, 2018;Ohlund et al, 2008), the condition in Himalayan stream networks is assumingly detrimental owing to limited research available on its interactions with natives.…”
Section: Introductionmentioning
confidence: 99%